2019
DOI: 10.1111/eve.13168
|View full text |Cite
|
Sign up to set email alerts
|

Treatment using cannabidiol in a horse with mechanical allodynia

Abstract: Summary A 4‐year‐old Quarter Horse mare was seen in the field by Colorado State University's Equine Sports Medicine Service for a 5‐week history of marked sensitivity to touch near the withers/shoulder region. On examination, the mare showed a marked adverse response to light touch over the caudal neck and withers region. Diagnostic imaging of the caudal neck, withers and shoulder region showed no significant abnormalities. Vital parameters, complete blood count and chemistry profile were also within normal li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…Even though limited empirical research has been carried out concerning the use of medical marijuana for pain treatment in domestic animals [10] and horses [11], the use of cannabis products in animals is expanding [12]. Of the cannabis products, cannabidiol (CBD), a non‐psychoactive compound found in cannabis sativa , seems to be one of the most promising therapeutic substances.…”
Section: Introductionmentioning
confidence: 99%
“…Even though limited empirical research has been carried out concerning the use of medical marijuana for pain treatment in domestic animals [10] and horses [11], the use of cannabis products in animals is expanding [12]. Of the cannabis products, cannabidiol (CBD), a non‐psychoactive compound found in cannabis sativa , seems to be one of the most promising therapeutic substances.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study of veterinary students in Canada, where marijuana has been legalised for general use, 56% of respondents believed that medical marijuana has a potential therapeutic value in animals, based on perceived evidence for the efficacy of medical marijuana in humans (Vogt et al 2019). The case report by Ellis and Contino highlights the potential benefits of modulating the endocannabinoid system and central pain sensitisation with cannabidiol (Ellis and Contino 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that the expression of the receptors in this localisation could be of particular relevance for future functional studies assessing the effects of cannabinoids in horses to treat pain. Ellis and Contino (2021) published a case study in the journal Equine Veterinary Education concerning a 4-year-old Quarter Horse mare with a 5-week history of strong sensitivity to touch near the withers/shoulder region. An insect bite was considered as a possible cause.…”
Section: Clinical Use Of Cbd In Horsesmentioning
confidence: 99%
“…The dose was, therefore, adjusted to the initial level and it was gradually decreased during a period of 2 months without the repeated presence of increased sensitivity. The maintenance dose was 150 mg once a day and the owner described a 90% improvement (Ellis and Contino 2021).…”
Section: Clinical Use Of Cbd In Horsesmentioning
confidence: 99%